The Effect of Product Quality and Shopee Service Quality on Repurchase Interest in Scarlett Products (Study on Students of Management Department, Faculty of Economics of Makassar State University) - Jenitalia, Andi Nadia; Ramli, Anwar; Haeruddin, M. Ilham Wardhana; Mustafa, Muh. Yushar (Entrepreneurship, Management, and Business Research Journal, 2024)
Produk Scarlett merupakan salah satu produk yang mampu bersaing dengan para competitor di pasaran sejak 2022. Fakta di lapangan memaparkan beberapa konsumen merasa sangat puas terkait dengan pelayanan serta produk Scarlett. Namun, ketidakpuasan konsumen juga pernah terjadi saat produk yang diterima konsumen pada saat pembelian tidak memiliki logo, sehingga hal tersebut memicu kecurigaan terkait original Scarlett. Minat beli ulang berkaitan dengan kualitas produk dan kualitas layanan. Tujuan dari penulisan ini ialah memberikan hasil analisis terkait dengan minat pembelian ulang yang dipengaruhi oleh kualitas layanan serta produk Scarlett. Jenis penelitian yang digunakan ialah menggunakan kuantitatif. Kesimpulan yang diambil berdasarkan hasil penelitian ialah (1) minat beli ulang Scarlett dipengaruhi oleh kualitas produk, hal tersebut berarti semakin baik kualitas produk dari body lotion scarlett yang baik dengan presepsi konsumen akan meningkatkan minat beli ulang; (2) minat beli ulang Scarlett dipengaruhi oleh kualitas pelayanan yang berarti peningkatan kualitas pelayanan dapat meningkatkan minat beli; (3) kualitas pelayanan serta produk sama-sama mempunyai pengaruh pada minat beli ulang Scarlett pada mahasiswa Manejemen FEB Universitas Negeri Makassar. Scarlett products are one of the products that have been able to compete with competitors in the market since 2022. Facts in the field show that several consumers feel very satisfied with Scarlett's services and products. However, consumer dissatisfaction has also occurred when the product received by consumers at the time of purchase does not have a logo, so this triggers suspicion regarding the original Scarlett. Repurchase interest is related to product quality and service quality. The purpose of this paper is to provide analytical results related to repurchase interest which is influenced by the quality of Scarlett's services and products. The type of research used is quantitative. The conclusions drawn based on the results of the study are (1) Scarlett's repurchase interest is influenced by product quality, this means that the better the product quality of Scarlett body lotion which is good with consumer perception will increase repurchase interest; (2) Scarlett's repurchase interest is influenced by service quality which means that increasing service quality can increase purchase interest; (3) service quality and products both have an influence on Scarlett's repurchase interest in Management students of FEB, Makassar State University.